Effect of Screw Configuration on the Recyclability of Natural Fiber-Based Composites - Vlasta Chyzna; Steven Rowe; James Finnerty; Trevor Howard; Christopher Doran; Shane Connolly; Noel Gately; Alexandre Portela; Alan Murphy; Declan M. Devine; Declan Mary Colbert (Fibers, 2025)
The burgeoning crisis of plastic waste accumulation necessitates innovative approaches towards sustainable packaging solutions. Polylactic acid (PLA), a leading biopolymer, emerges as a promising candidate in this realm, especially for environmentally friendly packaging. PLA is renowned for its compostable properties, offering a strategic avenue to mitigate plastic waste. However, its dependency on specific industrial composting conditions, characterized by elevated temperatures, humidity, and thermophilic microbes, limits its utility for household composting. This study aims to bridge the research gap in PLA’s recyclability and explore its feasibility in mechanical recycling processes. The research focuses on assessing the mechanical characteristics of PLA and PLA-based composites post-recycling. Specifically, we examined the effects of two extrusion methods—conical and parallel—on PLA and its composites containing 20 wt.% basalt fibers (BF). The recycling process encompassed repeated cycles of hot melt extrusion (HME), followed by mechanical grinding to produce granules. These granules were then subjected to injection moulding (IM) after 1, 3 and 5 recycling cycles. The tensile properties of the resulting IM-produced bars provided insights into the material’s durability and stability. The findings reveal that both PLA and PLA/BF composites retain their mechanical integrity through up to 5 cycles of mechanical recycling. This resilience underscores PLA’s potential for integration into existing recycling streams, addressing the dual challenges of environmental sustainability and waste management. The study contributes to the broader understanding of PLA’s lifecycle and opens new possibilities for its application in eco-friendly packaging, beyond the limits of composting. The implications of these findings extend towards enhancing the circularity of biopolymers and reducing the environmental footprint of plastic packaging.